2018
DOI: 10.5713/ajas.17.0170
|View full text |Cite
|
Sign up to set email alerts
|

Quality of steak restructured from beef trimmings containing microbial transglutaminase and impacted by freezing and grading by fat level

Abstract: ObjectiveThe objective of this research was to evaluate the physico-chemical, microbiological and sensorial qualities of restructured steaks processed from beef trimmings (grade I and II) and frozen beef (fresh beef as control and frozen beef).MethodsBeef trimmings from commercial butcher were collected, designated into 4 treatments differing in beef trimmings grade and freezing, processed into restructured steaks with 1% microbial transglutaminase and then analyzed for product quality.ResultsThe results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…One of the most widespread applications for TGs crosslinking activity in the food industry is the restructuring of meat and seafood by treatment of chopped muscle pieces with mTG and the polymerisation of muscle proteins (myofibrillar protein and myosin) to increase the textural characteristics and quality of the products [ 129 , 130 , 131 , 132 , 133 , 134 ]. Notably, mTG is not only exploited in meat processing, but also for the manufacture of dairy and bakery products, because of its considerable potential in improving the firmness, flavour, colour, texture, viscosity, elasticity, and water-binding capacity of aliments.…”
Section: Tgs Crosslinking Activity In Biotechnological Applicationmentioning
confidence: 99%
“…One of the most widespread applications for TGs crosslinking activity in the food industry is the restructuring of meat and seafood by treatment of chopped muscle pieces with mTG and the polymerisation of muscle proteins (myofibrillar protein and myosin) to increase the textural characteristics and quality of the products [ 129 , 130 , 131 , 132 , 133 , 134 ]. Notably, mTG is not only exploited in meat processing, but also for the manufacture of dairy and bakery products, because of its considerable potential in improving the firmness, flavour, colour, texture, viscosity, elasticity, and water-binding capacity of aliments.…”
Section: Tgs Crosslinking Activity In Biotechnological Applicationmentioning
confidence: 99%
“…The results obtained by Sorapukdee & Tangwatcharin [2018] and Baugreet et al [2018] showed that pieces of restructured beef processed with microbial TG could be bound together via cross-linking of myosin chains and actin.…”
Section: Introductionmentioning
confidence: 99%
“…The rising cost of beef products has led to the need for the rational use of low-value meat cuts and beef trimmings as restructured meat, as prepared from small cuts of meat. This approach allows for an increase in the yield of marketable products and enterprises to gain additional pro ts [Sorapukdee & Tangwatcharin, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…
44Введение Рост стоимости мясного сырья приводит к необходимости рационального использования низкосортного мяса с высоким содержанием соединительной ткани. Такой подход позволяет увеличить выход готовой продукции и получать предприятиям дополнительную прибыль [1,2].В последние годы в связи с интенсивным развитием биотехнологий особой популярностью пользуется ферментная обработка сырья [3][4][5]. Ферментативная модификация пищевых компонентов более приемлема для пищевой промышленности, чем общепринятые химические методы [6].
…”
unclassified
“…Введение Рост стоимости мясного сырья приводит к необходимости рационального использования низкосортного мяса с высоким содержанием соединительной ткани. Такой подход позволяет увеличить выход готовой продукции и получать предприятиям дополнительную прибыль [1,2].…”
unclassified